What do financial intermediaries do? - Allen, Franklin; Santomero, Anthony M (Journal of Banking & Finance, 2001)
This paper presents evidence that the traditional banking business of accepting deposits and making loans has declined significantly in the US in recent years. There has been a switch from directly held assets to pension funds and mutual funds. However, banks have maintained their position relative to GDP by innovating and switching from their traditional business to fee-producing activities. A comparison of investor portfolios across countries shows that households in the US and UK bear considerably more risk from their investments than counterparts in Japan, France and Germany. It is argued that in these latter countries intermediaries can manage risk by holding liquid reserves and intertemporally smoothing. However, in the US and UK competition from financial markets prevents this and risk management must be accomplished using derivatives and other similar techniques. The decline in the traditional banking business and the financial innovation undertaken by banks in the US is interpreted as a response to the competition from markets and the decline of intertemporal smoothing.